Financial Literacy, Individual Characteristic and Financial Inclusion: A Study on Lecturers in Palembang - Soejono, Fransiska; Mendari, Anastasia Sri (Future Science / FSH-PH Publications, 2022)
This study aims to analyze the effect of financial literacy, gender, age, income, and education on financial inclusion. This research involves university lecturers in the city of Palembang. The snowball sampling technique was used in this study and a total of 153 questionnaire forms were returned and could be processed. Hypothesis testing using multiple linear regression and SPSS assistance. The results showed that financial literacy and income had a positive and significant effect on financial inclusion, while other variables, namely gender, age, and education had no significant effect on financial inclusion. The implication is that the government through the Financial Services Authority (OJK) still needs to educate university lecturers in Palembang, especially those with below-average income, with the hope that the financial literacy of lecturers in Palembang will increase and all lecturers, especially those with low incomes, so that they have sufficient knowledge. to take the decision to have a financial product from a formal financial institution.